You don't look like a runner : female athletes' experiences of body expectations and ideals : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Psychology (Health Psychology) at Massey University, Albany, New Zealand - Grogan, Anneke (Massey University, 2021)
The aim of this thesis was to explore the experiences of female middle to long distance runners who felt they did not fit the ideals and expectations associated with being a runner using qualitative research methodologies. Eleven participants completed free-writing responses to the prompt ‘You don’t look like a runner’ with any experiences (past and/or present) they felt aligned with the statement. I then conducted semi-structured interviews with each of the participants, including questions stemming from their free-writing response. I identified four main themes through reflexive thematic analysis of the data: running was an important part of participants’ lives as Running is Part of My Identity and being told they did not look like runners sometimes led to the adoption of harmful behaviours to try and meet the idealised runner’s body. These harmful behaviours resulted in negative short-term and long-term health outcomes for some participants because Weight and Eating Behaviours Have an Impact on/are Impacted by Running. External sources played a key role in impacting how participants viewed their bodies and how they thought they were supposed to look because Those I am Surrounded by Impact how I Feel About My Body. The idealisation of a thin body will continue until the conflation between running success and the way a woman’s body looks is disrupted. Further research and work is needed in this space for meaningful changes to be made and Change is Needed for Future Generations of Women Runners.
Keywords: 520304 Health psychology